P669High pressure perfusion augments infarct size through a ROS dependent mechanism, protection by allopurinol. (15th July 2014) - Ytrehus, K; Boardman, NT; Martin-Armas, M; Norvik, JV; Jensen, TG; Toft, I
Abstract: Although uric acid is known as the most effective reactive oxygen species (ROS) scavenger within the extracellular space of the body, elevated serum concentration is correlated with inflammation, kidney pathology and impaired prognosis of heart disease. This experimental study in the isolated rat heart investigated the effect of A) extracellular uric acid and B) reduced intracellular uric acid and ROS by xanthine oxidase inhibition in the acute response to ischemic insult with or without a preconditioning stimulus (IPC) and following perfusion pressure overload. Tissue superoxide generation was visualized by dihydroethidium staining (DHE). The protective effects of ischemic preconditioning (IPC) against myocardial infarction were completely abolished when combined with uric acid (500μM) but not abolished with xanthine oxidase inhibitor allopurinol (1 nM). Perfusion pressure overload exacerbated ischemic injury as shown by increased infarct size (50.3±2.1 vs. 30.9±3.1, for HP vs. LP respectively) and increased DHE staining. The effect on infarct size was reversed following exposure to 500 μM uric acid (39.3±5.5 vs. 50.3±2.1, HP+uric acid vs. HP respectively). Inhibition of xanthine oxidase with allopurinol (1 mM) also reduced infarct size in pressure-overloaded hearts (41.1±3.9 vs. 50.3±2.1, HP+allopurinol vs. HP respectively). Furthermore, pressure overloaded hearts displayed increased phosphorylation of kinases Akt, ERK and GSK-3β by Western Blot, but this was unchanged following exposure to uric acid or allopurinol indicating that corresponding signaling pathways were not affected by the two treatments. We conclude that high pressure perfusion leads to increase in ROS load. The observed acute cardioprotection by uric acid or xanthine oxidase inhibition is probably due to reduction of ROS related factors.